AN INVESTIGATION INTO THE PROBLEMS FACED BY FIRST-YEAR STUDENTS AT FELTE, ULIS WHEN DOING PEER REVIEW IN ACADEMIC WRITING - Nguyen, Huy Hoang (2021)
Peer review has recently become an important component of both L1 and L2 writing classes due to its cognitive, affective, social and methodological benefits (Rollinson, 2005). In the context of ULIS, peer review is widely used as a tool to help students correct their drafts; however, there has not been much research into the problems that might reduce the effectiveness of the activity. This study aims at investigating the current problems that first-year students at FELTE, ULIS face when doing peer review in academic writing classes. The participants included 45 mainstream first-year students from two classes majoring in English Language Teacher Education and their two writing teachers. Data were collected via three instruments: observation of documents, survey-questionnaire (for student participants), and interview (for teacher participants) so as to triangulate the information from various aspects. The results showed that the students experienced troubles with all the seven potential problems, but the four most serious ones are lack of training from teacher, limited knowledge of English, imbalance between the two types of comments, and low learners’ investment. Teachers‟ attitude toward peer review, as well as their perceptions of the problems face by students, was also deeply analyzed. Finally, some suggestions to improve the effectiveness of the peer review activity were made for academic writing teachers and first-year students